گەشەکردنى سیستێمەکانى دەنگ و ووشە لە کن زارۆکان - ئەمین, سەروەت محەمەد (Sulaimani Journal for Humanities, 2000)
The first real time for a baby to start speaking is after one year from his birth. This is a result of a continuous attempt and training. It is a long-term process which starts since the baby's birth. This process passes through four stages: 1- Crying and whining 2. Babbling 3- Imitating Sounds 4- Clear speaking For example, during the first and second stages, it is a reaction of hearing Sounds. For baby cries when he feels hungry, wet, sleepy or when he has a pain some where. In the fourth month of his age he starts babbling. He expresses his feelings through long monologues in which all sounds are mixed up, even he produces some sounds which do not exist in the surrounding languages, or they are not part of the phonology of any language. In fact they are part of a system which he may have learned instinctively. Sometimes the sounds he produces may result in incompleted sounds. At the beginning differentiate between these sounds, one can hear only /oya/ /ah /, /eo /,/ ihe /, but after a short time his crying begins to have its characteristics and one can differentiate between Sounds. Some weeks later one can differentiate between sounds of crying whether it is because of hunger or being wet or having pain somewhere. Cognition of Sounds: If till that age, the baby produces, in his crying only the Vocals, after a period he produces the Consonants also. The first clear consonant is known as /m/ and its affixes like /am/, /ma/, then they are changed into /err/! like /orre/, /arra/, /or/, /ro/. This means that the baby learns labial sounds first, then dentals, then the other sounds. One of the first consonants that baby pronounces is guttural sounds, sounds pronounced by the back of the tongue and the plate, like /g/, /gh/. Tow Sylables Stage: After the first year a new stage starts with sound sequences like [ mama], [baba], [papa], [dada]. This stage puts an end to the babling stage. As I mentioned previously, in addition to the appearance of these sounds many times the baby stops speaking for a short period or sometimes for a long period. The Stage of Speaking: It is the stage of actuel speaking. Why does this stage start with sound sequences like /pa/. /ma/, /da/? Sound /a/ is one of the vocals that the mouth should be opened as wide as possible in order to be pronounced, while sound /p/ is an explosive labial consonant. In order to pronounce it the month should be closed as tight as possible. This is one of the cases of contrastive sounds in which both widely opening the mouth and closing it takes place, at the same time it shows clearly the difference between consonants and vowels.